Síntese e caracterização de hidroxiapatita dopada com terras raras (Eu³+ e Yb³+) com propriedades luminescentes - VIANA, Jailton Romão (2015)
The purpose of this study was to synthesize a bioceramic with base of hydroxyapatite and hydroxyapatite by inserting rare earth ions having luminescent properties. Hydroxyapatite (HAP), which is the main mineral that constitutues the bone tissue and represents about 5% of the total mass of an adult person. It is the bioceramic most studied among researchers for medical and dental applications, because they have important properties for biomaterials area, such as: biocompatibility and osteointegration. These properties make it one of the most suitable biomaterials for use in implants, prostheses, among others. The rare earths have luminescent properties with little efficiency when alone, needing a binder matrix (host) to absorb its received radiation energy and transfer the energy to the rare earth ions that, in turn, emit luminescence more intensely. The luminescence of an apatite doped with rare earth is valuable in biological applications such as luminescent markers. The methodology employed was the solid state reaction via calcination involved stoichiometric relationships between the reagents and doping of hydroxyapatite. The dopants were chosen for their fluorescent character and having high possibility of inclusion in the HAP matrix, replacing the Ca2+ ions. The techniques used contributed to verify and compare the formagtion, the structure and crystallinity of the samples. The results obtained from this research were satisfactory when compared with those found in the literature. The analyses of the diffraction of X - rays showed that there was the formation of hydroxyapatite and the dissolution of rare earth ions in the matrix, proven by the Rietveld refinement method. The insertion of the rare earth ions in the hydroxyapatite altered the average size of the crystallite, while increased the concentration of rare earths, the crystallite size decreased. The comparison of the Raman spectra of the doped samples strengthened the idea of the dissolution of the ions in the matrix of the hidoxiapatita demonstrated by fluorescence emission spectrum, because emitted luminescence signals with electronic transitions in the visible spectrum. The figures presented in the density were satisfactory, since they are close to the theoretical values. The increase in density of the samples doped with rare earth ions were also acceptable considering that the TR3+ ions have a higher density than the Ca2+ ions. The values found of the porosity are satisfactory in percentage relations, because the pores are intrinsic characteristics of bioceramic materials and enables adhesion property of the material to the immune tissue. The Fluorescence spectroscopy showed emission signs. Most fluorescence signal intensity occurred in the hydroxyapatite sample doped with europium and ytterbium (HAEu1Yb0,5) enabling its use as a probe or fluorescent marker. The dielectric measurements showed values befitting with the ones found in the literature, as well as the dielectric losses. The conductivity values presented are very low, enabling use of synthesized samples and being used dielectrics.